2010
DOI: 10.1007/s00425-010-1310-y
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones affect lateral root formation and root-hair elongation in Arabidopsis

Abstract: Strigolactones (SLs) have been proposed as a new group of plant hormones, inhibiting shoot branching, and as signaling molecules for plant interactions. Here, we present evidence for effects of SLs on root development. The analysis of mutants flawed in SLs synthesis or signaling suggested that the absence of SLs enhances lateral root formation. In accordance, roots grown in the presence of GR24, a synthetic bioactive SL, showed reduced number of lateral roots in WT and in max3-11 and max4-1 mutants, deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
385
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 446 publications
(409 citation statements)
references
References 52 publications
21
385
2
1
Order By: Relevance
“…2). Arabidopsis strigolactone mutants had shorter root hairs than the wild type and a significant increase in root hair length was observed upon exogenous GR24 treatment in wild-type and max3 and max4 mutant plants, whereas addition to max2 roots had no effect (Kapulnik et al 2011a). As observed in lateral root development, this MAX2-dependent root hair length phenotype is concentration-dependent and at high concentrations even the max2 mutant responds to GR24.…”
Section: Root Hair Length Is Enhanced By Strigolactonesmentioning
confidence: 80%
See 3 more Smart Citations
“…2). Arabidopsis strigolactone mutants had shorter root hairs than the wild type and a significant increase in root hair length was observed upon exogenous GR24 treatment in wild-type and max3 and max4 mutant plants, whereas addition to max2 roots had no effect (Kapulnik et al 2011a). As observed in lateral root development, this MAX2-dependent root hair length phenotype is concentration-dependent and at high concentrations even the max2 mutant responds to GR24.…”
Section: Root Hair Length Is Enhanced By Strigolactonesmentioning
confidence: 80%
“…Ruyter-Spira et al (2011) found that GR24 treatment prevented the transition of lateral root primordia from stage V to stage VI in both wild type and strigolactone biosynthesis mutants (except max4). In contrast, Kapulnik et al (2011a) suggest that the initiation of lateral roots was affected rather than the elongation or outgrowth, but this was highly dependent on the applied concentration of strigolactones. Although it is difficult to reconcile these two contrasting reports, part of the mechanism for strigolactone regulation of lateral root formation may result from changes in auxin transport capacity (reduction of PIN1 expression) (Ruyter-Spira et al 2011).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…A plethora of signal molecules, including those from other inhabitants of the soil are expected to be present. Interestingly, the chemical nature of the mycorrhizal symbiotic molecules identified so far points to their flexibility as signals: plants constitutively release the versatile strigolactones, which also act as germination inducers of parasitic plants [3and4] as well as hormones that are responsible for plant architecture [39]; and the active molecule produced by the AMFs mirrors the Nod factor released by the rhizobia. It seems that in the rhizospheric conversation, the same word might have different meanings depending on the context.…”
Section: Discussionmentioning
confidence: 99%